Thinking French translation : a course in translation method : French to English - Hervey, Sándor G. J.; Higgins, Ian (Thinking translation., 2002)
This new edition features material from business, law and literary texts. This is Essential reading for advanced undergraduates and postgraduate students of French, the book will also appeal to language students and tutors.